EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA UNTUK MENINGKATKAN EMPATI SISWA SMP NEGERI 8 PALOPO - Laelah, Nur; Fahmi, Ainul; Saqinah Galugu, Nur (IKIP Siliwangi, 2025)
This study aims to determine the effectiveness of group guidance services using the sociodrama technique in increasing the empathy of 7th-grade students at SMP Negeri 8 Palopo. The research applied a quantitative approach with a one-group pretest-posttest design. The sample consisted of 20 students with low empathy levels. The data collection instrument was an empathy scale questionnaire that had been tested for validity and reliability. Data were analyzed using the Paired Sample T-Test. The results showed a significant increase in students’ empathy levels after the intervention. The average pre-test score of 37.20 increased to 64.25 in the post-test. This proves that the sociodrama technique is effective in enhancing students’ empathy.